Immune sensitization during 1 year in the Antarctic high-altitude Concordia environment - Feuerecker, Matthias S.; Crucian, Brian E.; Quintens, Roel; Buchheim, Judith-Irina; Salam, Alex P.; Rybka, Ales; Moreels, Marjan; Strewe, Claudia; Stowe, Raymond; Mehta, Satish; Schelling, Gustav; Thiel, Manfred; et al. (Allergy, 2019)
Background Antarctica is a challenging environment for humans. It serves as a spaceflight ground analog, reflecting some conditions of long-duration exploration class space missions. The French-Italian Concordia station in interior Antarctica is a high-fidelity analog, located 1000 km from the coast, at an altitude of 3232 m. The aim of this field study was to characterize the extent, dynamics, and key mechanisms of the immune adaptation in humans overwintering at Concordia for 1 year. Methods This study assessed immune functions in fourteen crewmembers. Quantitative and phenotypic analyses from human blood were performed using onsite flow cytometry together with specific tests on receptor-dependent and receptor-independent functional innate and adaptive immune responses. Transcriptome analyses and quantitative identification of key response genes were assessed. Results Dynamic immune activation and a two-step escalation/activation pattern were observed. The early phase was characterized by moderately sensitized global immune responses, while after 3-4 months, immune responses were highly upregulated. The cytokine responses to an ex vivo stimulation were markedly raised above baseline levels. These functional observations were reflected at the gene transcriptional level in particular through the modulation of hypoxia-driven pathways. Conclusions This study revealed unique insights into the extent, dynamics, and genetics of immune dysfunctions in humans exposed for 1 year to the Antarctic environment at the Concordia station. The scale of immune function was imbalanced toward a sensitizing of inflammatory pathways.
First published: 06 July 2018
Gesehen am 03.07.2019